L'immigrazione in Sardegna - Zurru, Marco (UNICApress, 2023)
This volume collects the main results of an internal work of the FAMI-PRIMA Project, Regional Plan for Strengthening the Labor Integration of Migrants 2018-2020. Through a partnership with Anci Sardegna, the Autonomous Region of Sardinia (RAS), and the Sardinian Agency for Active Employment Policies (ASPAL), the project aims to foster better socio-work integration of applicants and holders of humanitarian, subsidiary and political asylum protection through the survey of the skills, competencies and capacities declared by themselves. Through the generous collaboration of linguistic-cultural mediators, a questionnaire capable of highlighting some socio-demographic characteristics of migrants, the universe of services used on the spot, and their desires regarding professional placement in the different segments of the Italian labor market was administered in the different provinces of the Island. The author elaborated, analyzed and commented on the research results by translating the skills declared by migrants according to the dictionary of the ISTAT CP2011 Classification of Occupations. Thus, the elements of continuity, but also those of rupture and novelty that characterize the migratory phenomenon in the island's labor market were highlighted, returning to policy makers the factual possibility of designing vocational training courses in line with the detected skills.